2023
DOI: 10.55705/cmbr.2022.365507.1072
|View full text |Cite
|
Sign up to set email alerts
|

Study of thyroid hormones effect on biochemical parameters of liver function in Iraqi patients

Abstract: This study was aimed to study the effect of thyroid hormones on some biochemical tests of liver function in Iraqi male patients and to study the relationship between them. A controlled study included 135 samples from patients and controls, group B, 45 patients with a liver disorder, and group C: 45 patients with a thyroid disorder, and group A: 45 healthy people (as the controls group). The study concluded that there were significant statistically significant differences for patients with liver disease, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A recent study by Jaafer et al (2023) [ 6 ] did not show any correlation between TSH, liver enzymes, or serum protein levels. The results of our study conform to the results of Jaafer et al (2023) [ 6 ]. Hypothyroidism and hyperthyroidism significantly affect thyroid function tests.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A recent study by Jaafer et al (2023) [ 6 ] did not show any correlation between TSH, liver enzymes, or serum protein levels. The results of our study conform to the results of Jaafer et al (2023) [ 6 ]. Hypothyroidism and hyperthyroidism significantly affect thyroid function tests.…”
Section: Discussionmentioning
confidence: 89%
“…Literature shows a positive association between thyroid hormones and liver function parameters [2][3][4][5]. A recent study by Jaafer et al ( 2023) [6] did not show any correlation between TSH, liver enzymes, or serum protein levels. The results of our study conform to the results of Jaafer et al (2023) [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported an important role of the Bcl-2 family protein in the regulation of apoptosis and cell survival (50). In this regard, the effect of medicinal plants has also been considered (51)(52)(53)(54)(55)(56)(57)(58)(59)(60). In further elucidating the molecular mechanism of PJME-induced apoptosis, the mRNA expression of Bax, Bcl-2 and caspase-3 genes were measured.…”
Section: Discussionmentioning
confidence: 99%